Thermodynamic analysis and parameter estimation of a high-temperature industrial heat pump using a new binary mixture. (25th February 2018) - Yu, Xiaohui; Zhang, Yufeng; Kong, Lingteng; Zhang, Yan
Highlights: An optimized high-temperature heat pump using MF-1 was designed and built. A function for MF-1 was defined to achieve accurate control of superheat. Experimental investigations of the HTHP were carried out at high temperature level. Energy and exergy analyses were conducted to evaluate the performance of the HTHP system. A parameter estimation method was developed to predict the performance of the HTHP system. Abstract: An optimized high-temperature heat pump (HTHP) adopting a new binary mixture named MF-1 as working fluid was designed and built for industrial waste heat recovery. A new function for MF-1 was defined to achieve accurate control of superheat in the expansion valve. Experimental investigations of this heat pump were carried out at high temperature level of 40–60 °C on evaporation unit and 70–110 °C on condensing unit. Energy and exergy analyses provided insight on the quantity and quality of energy conversion of the HTHP system in different running conditions. Based on the energy and exergy analyses, this study investigated how the heat-source temperature and heat-sink temperature have effect on the performance of each component and the HTHP system. Additionally, a parameter estimation method based on the regression analysis was developed to evaluate the performance of the HTHP system. A comparison of the experimental and simulated results was made to demonstrate the reliability of the presented method. The simulated results indicated that the HTHP system using MF-1 can produce heat at the temperature of 120 °C with good performance.